Atherosclerotic Vascular Events in a Multinational Inception Cohort of Systemic Lupus Erythematosus (SLE) - UROWITZ, M. B. (2010)
OBJECTIVE: To describe vascular events during an 8 year follow-up in a multicentre SLE inception cohort and their attribution to atherosclerosis. METHODS: Clinical data including co-morbidities are recorded yearly. Vascular events are recorded and attributed to atherosclerosis or not. All events met standard clinical criteria. Factors associated with atherosclerotic vascular events were analysed using descriptive statistics, t-tests and χ(2). Stepwise multivariate logistic regression was used to assess the association of factors with vascular events attributed to atherosclerosis. RESULTS: Since 2000, 1249 patients have been entered into the cohort. There have been 97 vascular events in 72 patients. These include: myocardial infarction (13), angina (15), congestive heart failure (24), peripheral vascular disease (8), transient ischemic attack (13), stroke (23), pacemaker insertion (1). Fifty of the events were attributed to active lupus, 31events in 22 patients were attributed to atherosclerosis, and 16 to other causes. Time from diagnosis to first atherosclerotic event was 2.0 ± 1.5 years. Compared to patients followed for 2 years without atherosclerosis events (615), at enrolment patients with AVE were more frequently Caucasian, male, older at diagnosis of SLE, obese, smokers, hypertensive and had a family history of coronary artery disease. On multivariate analysis only male gender and older age at diagnosis were associated factors. CONCLUSION: In an inception cohort with SLE followed for up to 8 years there were 97 vascular events but only 31 were attributable to atherosclerosis. Patients with atherosclerotic events were more likely to be male and to be older at diagnosis of SLE.